A note on cobordisms of algebraic knots - Bodnár, J; Celoria, D; Golla, M (Mathematical Sciences Publishers, 2017)
In this note we use Heegaard Floer homology to study smooth cobordisms of algebraic knots and complex deformations of cusp singularities of curves. The main tool will be the concordance invariant $ν^+$: we study its behaviour with respect to connected sums, providing an explicit formula in the case of L-space knots and proving subadditivity in general.